Community-based language learning : a framework for educators - Clifford, Joan; Reisinger, Deborah Streifford, 1969- (Georgetown University Press, 2019)
Community-based Language Learning offers the first manual for world language educators interested in community-based learning (CBL). CBL includes pedagogical approaches that connect academic learning objectives with experiential learning, ranging from reciprocal partnerships with the community (e.g., community engagement, service-learning) to one-directional learning situations (e.g., community service, site visits, etc.).